The Occurrence of Clostridium difficile Toxin in Ulcerative Colitis - Iizuka, M.; Igarashi, K.; Chiba, M.; Kodama, K.; Tsurui, N.; Horie, Y.; Masamune, O.; Arakawa, H. (Nippon Daicho Komonbyo Gakkai Zasshi, 1988)
The occurrence of Clostridium dificile toxin in feces was studied in 17 cases of ulcerative colitis (mild, 5 ; moderate, 11 ; severe, 1) (initial attack, 1 ; relapsing-remitting, 15 ; chronic persistent, 1). Toxin was demonstrated in only two of the 17 cases (11.8%). In one of these two cases, antibiotics had been administered beforehand and the diagnosis made was ulcerative colitis with antibiotic-associated pseudomembranous colitis. In the other case, toxin was positive only on admission and became negative three days later without treatment. There was no correlation between the presence of the toxin and the severity of ulectative colitis. Since toxin was negative in all of 11 cases treated with sulfasalazine, administration of this agent was unrelated to the presence of the toxin. Our results suggest that Clostridium difficite toxin is not related to the onset or relapse of ulcerative colitis.